Stress-testing inflation exposure: Systemically significant prices and asymmetric shock propagation in the EU28 - Leonhard Ipsen; Armin Aminian; Jan Schulz-Gebhard (Bamberg University, Bamberg Economic Research Group (BERG), 2023)
Building on the seminal paper of Weber et al. (2022), we provide a stress-test framework of inflation exposure and apply it to the EU28. This adds a yet unrecognised dimension to the latest calls for supply chain stress-tests. We address both the ex- and internal dimensions of inflation exposure for the former EU28 countries within global production networks via a Leontief price model. Using data from the World Input Output Database, we confirm the existence of systemically significant sectors for the overall price level in the EU28, EU periphery and core, respectively. We show that while the direct price effects of various sectors on the respective consumption shares are significant, about two-thirds of the overall effects are indirect and thus a result of higher-order propagation within the production network. It crystallizes that two properties (size and centrality) may render a sector systemically significant. Breaking down the geographical component, we show that the indirect effect is even larger for peripheral countries, which points to a higher exposure to world market prices. By tracing individual shock trajectories, we confirm this hypothesis: price volatility originating from the core countries impacts the peripheral countries more than vice versa. In addition to this, our method to recover consumption substitution effects shows that substitution is much more limited in the European periphery. Overall, we show consumers in peripheral countries are relatively more exposed to price volatility.
Keywords: 330; inflation; stress-test; input-output analysis; Europe